New Insights Into the Stratigraphic Setting of Paleozoic to Miocene Deposits - Case Studies From the Persian Gulf, Peninsular M 2019
DOI: 10.5772/intechopen.81402
|View full text |Cite
|
Sign up to set email alerts
|

Paleoecology and Sedimentary Environments of the Oligo-Miocene Deposits of the Asmari Formation (Qeshm Island, SE Persian Gulf)

Abstract: The Asmari Formation is composed of limestones, marly limestones, and marls, whose subsurface thickness in this region is about 148 m. Two assemblage zones have been recognized through the distribution of large foraminifera in the study area, indicating a Late Oligocene (Chattian)-Early Miocene (Aquitanian) age. The gradual facies changes and the lacking of turbiditic deposits show that the Asmari Formation was deposited in a carbonate ramp environment. Based on the depositional textures and petrographical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Sarvak Formation is known as a reservoir rock and Kazhdomi Formation is known as a very important source rock in most of Iran's oil fields [12,44]. Knowing the facies and sequences of these two formations along with their lateral changes in understanding them better is necessary to calculate the production and accumulation of hydrocarbons [15,36].…”
Section: Introductionmentioning
confidence: 99%
“…Sarvak Formation is known as a reservoir rock and Kazhdomi Formation is known as a very important source rock in most of Iran's oil fields [12,44]. Knowing the facies and sequences of these two formations along with their lateral changes in understanding them better is necessary to calculate the production and accumulation of hydrocarbons [15,36].…”
Section: Introductionmentioning
confidence: 99%
“…Sarvak Formation is known as a reservoir rock and Kazhdomi Formation is known as a very important source rock in most of Iran's oil fields (4,5). Knowing the facies and sequences of these two formations along with their lateral changes in understanding them better is necessary to calculate the production and accumulation of hydrocarbons (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards this Formation were studied by Richardson (1924), De Böckh et al (1929), Lees (1933), Zabihi Zoeram et al (2013), Aiello (2019), Monjezi et al (2019), that revised the age of Asmari Formation to the Oligocene-Miocene. This formation was defined regionally based on lithological and paleontological analysis (James and Wynd 1965;Adams and Bourgeois 1967;Motiei 1993;Aiello 2019;Hosseini Asgarabadi et al 2019;Sajadi and Rashidi 2019) and was deposited on a tropical platform, which covered southwestern Iran and parts of Iraq (James and Wynd 1965). More recent studies of the Asmari Formation were reported by (Ehrenberg et al 2007;Van Buchem et al 2010;Rahmani et al 2012;Ehrenberg and Baek 2019;Farshi et al 2019;Gharechelou et al 2020).…”
Section: Introductionmentioning
confidence: 99%